Maiestas Serena: Roman court cameos and early imperial poetry and panegyric - Smith, RRR (Cambridge University Press, 2021)
This article offers an account of Roman imperial cameos as an archaeological category, and argues that the production of large high-quality cameos was more restricted in time than currently allowed; that the controversial dates and subjects of individual cameos need to be set in the wider sequence of the main examples; and that early imperial praise poetry sits in relationship to court cameos in a way that can be usefully investigated around their shared concern to understand the particular character of imperial divinity. An Appendix gives details of forty-one examples illustrated and discussed.